(3GdbGfhfs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3JMOjO GdWH GdKGfi ai ehVhYGJ GdWH GdYde GdKGfi ai GdGQcGf GdJYdje GdKGdK s
(3BNQgG (B:s
(3GdOQNei , SJI ChKhdGJ , cd ChKhd KdGKI bQGQjW , cd bjQGW SHY TYjQGJ , hGdKdGKI ChKhdGJ JSYI bQGQjW , GdbhGfhS ChbjI hfUa s
(3fSNI KGdKI JTJed Ydi GdcJH GdNeSIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B175 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GdWHs